EVALUASI PERTUMBUHAN FISIK DAN PERAN GURU PJOK DALAM MENDUKUNG TUMBUH KEMBANG SISWA DI SEKOLAH DASAR: STUDI DI SDN 11 BIREUEN - Suhendar, Aris; Amiruddin; Yeni Marlina; Razali (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2025)
This paper investigates the critical role of Physical Education (PE) teachers in monitoring and supporting the physical growth of elementary school students, a crucial period for development. The study focuses on evaluating the current physical growth status (nutritional status) of students and analyzing the specific practices, challenges, and perceived roles of PE teachers in this domain.This study employed a mixed-methods approach (explanatory sequential design), conducted at SDN 11 Bireuen. Quantitative data involved anthropometric measurements (height-for-age and BMI-for-age) from 150 students in grades 4-6. Qualitative data were gathered through semi-structured interviews with 3 PE teachers and classroom observations.Quantitative data were descriptively analyzed using WHO AnthroPlus to generate Z-scores for nutritional status. The qualitative interview data were analyzed using thematic analysis with open coding.The results indicate a double burden of malnutrition: 18% of students were identified as 'thin' (kurus) and 12% as 'overweight' (gemuk). The qualitative findings identified three main roles for PE teachers: (1) Motivator and Educator, (2) Limited Facilitator (due to resource constraints), and (3) Untapped Collaborator (minimal coordination with health services/parents). Teachers perceive their primary role as skill development rather than health monitoring. Based on the findings, a significant gap exists between the potential and actual role of PE teachers in growth monitoring at SDN 11 Bireuen. A systematic, school-based framework is required to integrate anthropometric evaluation into routine PE activities, supported by adequate resources and inter-stakeholder collaboration.